2014
DOI: 10.1159/000354427
|View full text |Cite
|
Sign up to set email alerts
|

Standard-Tract Combined with Mini-Tract in Percutaneous Nephrolithotomy for Renal Staghorn Calculi

Abstract: Purpose: To compare the safety and efficacy of standard-tract combined with mini-tract to single standard-tract in percutaneous nephrolithotomy (PCNL) for renal staghorn calculi. Methods: The records of 216 patients with staghorn calculi (110 (50.9%) had complete and 106 (49.1%) had partial) who received PCNL were reviewed retrospectively. 58 patients received standard-tract combined with mini-tract PCNL (group A) and 158 patients underwent single standard-tract PCNL (group B). Both groups had comparable demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
13
0
2
Order By: Relevance
“…When removing multiple dispersed kidney stones, larger devices are hard to use in a small space, leading to the need for multiple percutaneous tracts [7]. Due to a higher need for multiple percutaneous tracts to completely remove stones and larger sized percutaneous tract used, standard PCNL causes more bleeding and injuries [8]. …”
Section: Introductionmentioning
confidence: 99%
“…When removing multiple dispersed kidney stones, larger devices are hard to use in a small space, leading to the need for multiple percutaneous tracts [7]. Due to a higher need for multiple percutaneous tracts to completely remove stones and larger sized percutaneous tract used, standard PCNL causes more bleeding and injuries [8]. …”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that tubeless PCNL is a viable alternative to tubed PCNL in uncomplicated cases and there is no evidence that suggests that a patient's safety is compromised by the omission of postoperative nephrostomy [10,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…Wang ve ark. 'ları, staghorn taşlarda mini-PNL içeren kombine yaklaşımın taşsızlık oranını %89.7'ye kadar yükselttiğini bildirmiştir (27).…”
Section: Perkütan Nefrolitotomiunclassified